2016
DOI: 10.1016/j.fsi.2016.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Sea lice vaccine development based on an immunogenic peptide derived from the ribosomal protein P0

Abstract: Sea lice (Copepoda, Caligidae) are the most widely distributed marine pathogens in the salmon industry. Vaccination is considered an efficient, environmentally safe and economically sustainable alternative for control of ectoparasite infestations. Although emerging sea lice proteins have been identified recently, and have been proposed as potential targets for generating protective molecules, only a limited number of them have been evaluated in vaccine trials with unsuccessful results. On the other hand, more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Anticlotting-related proteins are considered potential targets for the development of new drugs and vaccines to control and prevent ectoparasites such as ticks (Oleaga et al, 2017), mosquitos (Popova-Butler and Donald, 2009; Tetreau et al, 2012), Schistosoma (Delcroix et al, 2006), and sea louse (Carpio et al, 2011, 2016). However, the hosts of these parasites are vertebrates, in which the composition of the coagulation system differs from that of invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Anticlotting-related proteins are considered potential targets for the development of new drugs and vaccines to control and prevent ectoparasites such as ticks (Oleaga et al, 2017), mosquitos (Popova-Butler and Donald, 2009; Tetreau et al, 2012), Schistosoma (Delcroix et al, 2006), and sea louse (Carpio et al, 2011, 2016). However, the hosts of these parasites are vertebrates, in which the composition of the coagulation system differs from that of invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, to further antigen discovery, a related parasitic species can be used that have a permissible animal model for vaccine trial evaluations. In this manner homologous target proteins can be identified that may confer cross-species protection such as subolesin/akarin and P0 antigens (Moreno-Cid et al, 2013 ; de La Fuente and Contreras, 2015 ; Mallon et al, 2015 ; Carpio, 2016 ; Villar et al, 2017 ). Additional in vitro feeding systems for ectoparasites such as ticks, lice, mites and mosquitoes have become valuable tools for parasite study and development of antiparasitics by mitigating the requirement for host animal challenges and affording a platform for high-throughput studies (i.e., infection studies, gene knock-down and chemical assays) (Kessler et al, 2014 ; Bartley et al, 2015 ; Sangaré et al, 2016 ; Agramonte et al, 2017 ; Kim et al, 2017 ; Krull et al, 2017 ; Trentelman et al, 2017 ).…”
Section: Metazoan Vaccine Development: Identification To Formulationmentioning
confidence: 99%